Salafi and Islamist Londoners: Stigmatised minority faith communities countering al-Qaida - Lambert, Robert (Crime, law and social change, 2008)
The paper highlights the paradoxical position of certain Salafi and Islamist communities in London who have consistently demonstrated skill, courage and commitment in countering al-Qaida propaganda and recruitment activity while simultaneously facing ill-founded criticism from other Muslim communities and secular political lobbyists for creating the conditions that gave rise to the al-Qaida phenomena. In doing so the paper compares the experience of Salafi and Islamist communities living in London during an ongoing terrorist campaign by al-Qaida with Jewish and Irish Catholic communities living in London during earlier terrorist campaigns against the UK’s capital city. In each instance community policing is shown to have a crucial role to play in terms of reassurance for minority faith communities and the prevention of terrorism. However, the intersection between policing and counter-terrorism is shown to produce tensions that may weaken minority community confidence in policing and thereby reduce proactive community support for counter-terrorism measures. At this intersection a London policing initiative is shown to have developed proactive counter-terrorism partnerships with Salafi and Islamist community groups of a pioneering nature. In consequence the same critics who conflate Salafis and Islamists with an urgent terrorist threat to London have accused this policing initiative of appeasing extremism.